NANO-SIZED La0.5Ca0.5CoO3-MEDIATED REDUCTION BY NaBH4 OF ARYL NITRILES TO BIS-(BENZYL) AMINES - Bavandi, Hossein; Shiri, Ali; Tavakkoli, Haman (Journal of the Chilean Chemical Society, 2017)
Nano-sized La0.5Ca0.5CoO3 perovskite, which was produced via the sol-gel method, was an efficient heterogeneous catalyst in combination with NaBH4 for the rapid chemoselective reduction of aryl nitriles to bis-(benzyl)amines at 40 ºC in good to excellent yields. The physico-chemical properties of the catalyst were characterized by means of differential thermal analysis (DTA), thermogravimetric analysis (TGA), X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDX) and particle size distributions images. The results show that nanoparticles have regular shapes with well-defined crystal faces with an average size of 30 nm.